9 Comparative Study Between Propofol-Ketamine and Propofol-Butorphanol For TIVA Techinque in Short Surgical Procedures - Shruti Gupta; Rajdeep Kour; Seema Sambyal (Dr. Annil Mahajan, 2022)
Background: Total intravenous anaesthesia (TIVA) is a technique in which induction and maintenance of anaesthesia is achieved with intravenous (IV) drug alone avoiding volatile agents. In this process, the patient either breaths spontaneously or with bag mask ventilation combined with oxygen. AIMS AND Objective: To compare Propofol -Ketamine and Propofol -Butorphanol for TIVA in short surgical procedures in terms of their Hemodynamic stability, Postoperative sedation, Pain on injection with Propofol & Post operative nausea and vomiting. Material And Methods: This prospective, comparative study was conducted in 50 patients (18 - 60 years of age), ASA grade I and II, scheduled for elective surgery of duration less than 1hour. Patients were randomly divided into two groups : Group B-P receive inj.Butorphanol 20 ug/ kg + inj.Propofol 1.5 mg/kg and Group K-P receive inj. Ketamine 1mg/kg + inj. Propofol 1.5 mg/kg and Anesthesia was maintained with injection Propofol in the dose of 9mg/kg/hour. Results: Demographic data were comparable between two groups. Both groups were comparable in Hemodynamic parameters however in Group-BP there was decrease in mean blood pressure which was statistically insignificant. The incidence of sedation was more in group BP (36%) as compared to group KP (24%) but difference was statistical insignificant. In group BP, the incidence of pain was 4%, where as in group KP it was 36 % and this was statistical significant and the incidence of PONV is comparable in both groups. Conclusion: we concluded that both groups were comparable in terms of their Hemodynamic stability, Postoperative sedation and PONV but the Pain on injection with Propofol was significantly less in group BP (p value <0.01)